(untitled) (Tribhuvan University Journal of Microbiology, 2020)
Objectives: The objective of this study was designed to focus the prevalence, detection and identification of intestinal parasites and its associated factors among pregnant women. Methods: Total 264 stool samples were collected in a labeled dry, clean disinfectant free wide mouthed plastic container during antenatal visits at Ram Janaki Hospital, Janakpurdham and were examined by macroscopically and microscopically. The detection and identification of protozoal cysts, oocysts, trophozoites and helminthic eggs or larva was done by wet preparation and formalether sedimentation concentration technique. The data was analysed using SPSS 20 version and Microsoft Excel 2007. A Chi-square test was performed to predict the parasite detection using predictor variables. The p-values <0.05 was considered as significant. Results: The prevalence of intestinal parasitosis among pregnant women was 42%. There was positive association of symptoms of intestinal parasitosis among pregnant women (p < 0.05). The most predominant intestinal parasites among study participants were E. histolytica (20%) slightly dropped by G. lamblia (16%) followed by Hook worm (13%) and A. lumbricoides (11%). The correlation between all the variables with intestinal parasites presence and absence was statistically significant (p<0.05) but statistically insignificant for age and consumption of green leafy vegetables (p>0.05). Conclusion: The overall prevalence of intestinal parasitosis was relatively moderate. Lack of awareness, low hygienic and sanitation habits regarding parasitic infections were the major determinant factors for higher prevalence. Improving sanitation, awareness creation and public health programes should be organized at regular interval in community.